INVESTIGATING THE EFFECT OF HIGH AND LOW WIND SPEED ON SURPLUS NET RADIATION IN MAKURDI, NIGERIA: AN IMPLICATION TO ENERGY IMBALANCE (FUDMA JOURNAL OF SCIENCES, 2020)
This study aims at investigating the effect of wind speed on net radiation by conditioning the chance occurrence of surplus net radiation on high and low wind speed in Makurdi, Nigeria. A two – state (surplus net radiation conditioned on high wind speed and surplus net radiation conditioned on low wind speed) Markov Chain model was developed and used in the course of this work. The result revealed; net radiation is surplus all through the year, no definite linear trend between net radiation and wind speed and two extreme results of the Markov Chain model. This include; a steady state or long run chance of 62% surplus net radiation conditioned on low wind speed and 38% surplus net radiation conditioned on high wind speed occurring in the month of January and April. Further analysis with the model showed that it takes 2.44 days for surplus net radiation conditioned on high wind speed and 1.69 days for surplus net radiation conditioned on low wind speed on the average to reoccur from January – December. Thus, resulting to increase in air temperature in Makurdi all through the year.
Keywords: Surplus net radiation, steady state, Markov Chain, wind speed, Penman-Monteith